THE IGNORANCE OF INDIGENEOUS PROPERTY RIGHTS THROUGH THE RESETTLEMENT PROGRAM IN INDONESIA - Arifah Arifah; Mutmainnah Mutmainnah (Fapetrik-UMPAR, 2018)
Based on consideration of the inequality of population distribution between the island of Java, Indonesia's population policy focused on the equal distribution of the population with the application of transmigration policies. Transmigration policy in Indonesia is not only about population policy, but also is part of a strategy for economic modernization and the introduction of plantation markets outside Java. The purpose of this study was to analyze the impact of transmigration policies on the environment and local residents. This research is a descriptive study by trying to describe the impact of the population equalization policy in Indonesia. Based on this research shows that the ecological impact arising from this transmigration policy is deforestation and contributes greatly to the loss of forest areas. In addition, this population policy has an impact on the local population. The most common social conflict between local residents and transmigrants is the marginalization and loss of local culture, competition in business aspects and lack of concern from the government for local residents.